The effect of new metro stations on local land use and housing prices: The case of Wuhan, China. (July 2019) - Tan, Ronghui; He, Qingsong; Zhou, Kehao; Xie, Peng
Abstract: The metro system is an important means of transportation for urban residents in mega-cities in China, where not all families can afford an automobile and there are policy restrictions on private cars. Numerous empirical studies have investigated the implicit prices of metro stations in China. However, few have systematically examined the influence of the proximity of a metro station on housing prices. More importantly, the potential endogeneity of metro station placement is always neglected, which means that the validity of the reported causal effects of the distance to the metro station on housing prices must be questioned. To investigate whether households value being close to a metro station because closeness generates fundamentally positive externalities, we analyze the main changes in land use around metro stations before and after new metro lines are built, based on high-resolution images of Wuhan in China provided by Google Earth. The results suggest that the opening of new metro stations revitalizes land around suburban stations more than it does around central stations. However, the area around central stations exhibits a greater population increase than does the area surrounding suburban stations before a new line opens. The results for suburban and central stations seem to be paradoxical, suggesting that the cross-sectional regression using the full sample may be misleading. An additional before-and-after evaluation based on second-hand housing sales data in Wuhan indicates that households do value metro station proximity. Using the case of line 6, we show that opening new metro stations significantly increases housing prices in nearby areas. This influence extends to 1600 m from new metro stations. Moreover, second-hand housing within 1600 m of metro stations is 7–14% more valuable than its more remotely located counterparts. These findings suggest that local metro planners in China should not only recognize the importance of the metro for raising land-sector revenue but also focus on the location choice and spatial distribution of metro stations from the perspective of residents' interests. Highlights: Opening metro stations facilitates land revitalisation around greenfield stations Opening new stations leads to greater population growth for infill stations. Our innovative methods overcome the risk of endogeneity effects in analysis. Wuhan households value metro station proximity Metro stations cause a property price increase of up to 13.9% for nearby homes.